Groundwork for social-ecological transformations: the social contract, global governance and the meaning of time : constructive criticism of the WBGU report world in transition - a social contract for a great transformation - Manstetten, Reiner; Kuhlmann, Andreas; Faber, Malte; Frick, Marc (Discussion paper, 2021)
A decade ago, the German Advisory Council to the Federal Government on Global Environmental Change (Wissenschaftlichen Beirats der Bundesregierung für Globale Umweltveränderungen - WBGU) published its main report. This attempt to take stock in 2011 made an impact and provided orientation on both a national and international scale. The WBGU report did not hold back: It aimed to show the urgent need for change in terms of sustainable development through the interplay of politics, economy, society and nature. The central message was: We need a "social contract for a Great Transformation", and it must be implemented by 2021. How is the report to be assessed today? We will summarise the positions of the WGBU report, cite its merits, and comment on them critically and constructively. Our approach examines the five main themes of the report: the global social contract; global governance using the example of the Paris Climate Agreement; acceptance by those involved and affected; the urgency of economic, political and social action; and the concept of the Great Transformation. In our critique, we suggest ways to constructively elaborate on the ideas laid out in the WBGU report, ideas that were not thought through to the end. Our focus lies particularly on how to deal with time and the concept of the Great Transformation. In doing so, we will also address the significance of technical advances, innovation and our own ignorance. The title of the report uses the term "Great Transformation" which acts as a leitmotif throughout. Put forth by Karl Polanyi (1941/44), this term, as used in the WBGU's parlance, is intended to address the far-reaching changes that a regulatory state would have to undertake, along with the participation of the global citizenry, in order to overcome the ecological crisis of the coming decades. In our conclusion, we argue that the idea of a uniformly planned and comprehensively attainable transformation of the current situation is inadequate. Instead, we have observed that different actors in different places have worked at different speeds not on a Great Transformation but on a multitude of social-ecological transformation processes. The effectiveness of such movements - which often emerge spontaneously - has grown to the present day. This gives us hope.